2023
DOI: 10.5603/mrj.97187
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of double vs. standard empagliflozin dose for METabolic syndromE tReatment (DEMETER — SIRIO 11) study. Rationale and protocol of the study

Jacek Kubica,
Aldona Kubica,
Zofia Grąbczewska
et al.

Abstract: Complex metabolic disorders associated with obesity and diabetes pose a serious therapeutic challenge.The DEMETER-SIRIO 11 study is a phase III, multicenter, randomized, open-label, investigator-initiated clinical trial with a 6-month follow-up aimed at performing a comparative evaluation of the effect of two empagliflozin doses (10 mg vs. 20 mg) on selected metabolic parameters in patients with metabolic syndrome. The primary hypothesis of the study is that a higher dose of empagliflozin will result in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…Metabolic syndrome (MetS) including obesity, hypertension, impaired glucose metabolism, and elevated non-high-density lipoprotein cholesterol level due to increasing prevalence and serious impact on clinical outcomes constitutes a significant health and social problem [1]. Recently several papers published in "Medical Research Journal" presented different therapeutic approaches in this subset of patients [2][3][4][5][6].…”
Section: To the Editormentioning
confidence: 99%
“…Metabolic syndrome (MetS) including obesity, hypertension, impaired glucose metabolism, and elevated non-high-density lipoprotein cholesterol level due to increasing prevalence and serious impact on clinical outcomes constitutes a significant health and social problem [1]. Recently several papers published in "Medical Research Journal" presented different therapeutic approaches in this subset of patients [2][3][4][5][6].…”
Section: To the Editormentioning
confidence: 99%
“…A review of the PubMed database showed that the number of publications on MetS is growing rapidly, reaching over 106,000 publications this year. In the current issue of the Medical Research Journal, as many as four publications concern various treatment strategies for patients with obesity and metabolic syndrome [2][3][4][5]. The first one is the rationale and protocol of the DEMETER -SIRIO 11 study that is aimed at comparative evaluation of the effect of two doses of empagliflozin (10 mg vs. 20 mg) on reduction of BMI and HbA1c in patients with MetS.…”
mentioning
confidence: 99%
“…The first one is the rationale and protocol of the DEMETER -SIRIO 11 study that is aimed at comparative evaluation of the effect of two doses of empagliflozin (10 mg vs. 20 mg) on reduction of BMI and HbA1c in patients with MetS. The study is designed as a phase III, multicenter, randomized, open-label, investigator-initiated clinical trial with a 6-month follow-up [2]. The second publication is a report of study results aimed to determine whether the volume of the resected part of the stomach correlates with postoperative results after 1-year follow-up.…”
mentioning
confidence: 99%